Potential role of odanacatib in the treatment of osteoporosis - Ng KW (Dove Medical Press, 2012)
Kong Wah NgDepartment of Endocrinology and Diabetes and St Vincent’s Institute, St Vincent’s Hospital, Fitzroy, Victoria, AustraliaAbstract: Cathepsin K is a key enzyme involved in the degradation of organic bone matrix by osteoclasts. Inhibition of bone resorption observed in human and animal models deficient for cathepsin K has identified this enzyme as a suitable target for intervention by small molecules with the potential to be used as therapeutic agents in the treatment of osteoporosis. Odanacatib (ODN) is a nonbasic selective cathepsin K inhibitor with good pharmacokinetic parameters such as minimal in vitro metabolism, long half-life, and oral bioavailability. In preclinical studies, ovariectomized monkeys and rabbits treated with ODN showed substantial inhibition of bone resorption markers along with increases in bone mineral density (BMD). Significant differences were observed in the effects of ODN treatment compared with those of other antiresorptive agents such as bisphosphonates and denosumab. ODN displayed compartment-specific effects on trabecular versus cortical bone formation, with treatment resulting in marked increases in periosteal bone formation and cortical thickness in ovariectomized monkeys whereas trabecular bone formation was reduced. Furthermore, osteoclasts remained viable. Phase I and II studies conducted in postmenopausal women showed ODN to be safe and well tolerated. After 5 years, women who received ODN 50 mg weekly continuously from year 1 (n = 13), showed BMD increases from baseline of 11.9% at the lumbar spine, 9.8% at the femoral neck, 10.9% at the hip trochanter, and 8.5% at the total hip. Additionally, these subjects maintained a low level of the urine bone resorption marker N-terminal telopeptide/creatinine (-67.4% from baseline) through 5 years of treatment, while levels of serum bone-specific alkaline phosphatase remained only slightly reduced relative to baseline (-15.3%). In women who were switched from ODN to placebo after 2 years, bone turnover markers were transiently increased and BMD gains reversed after 12 months off medication. Adverse experiences in the ODN-treated group were not significantly different from the placebo group. In conclusion, available data suggests that cathepsin K inhibition could be a promising intervention with which to treat osteoporosis. Ongoing studies are expected to provide information on the long-term efficacy in fracture reduction and safety of prolonged treatment with ODN.Keywords: cathepsin K, selective cathepsin K inhibitors, bone remodeling, osteoclast, bone turnover markers